Mallard Anas platyrhynchos lead poisoning risk in central Portugal - Rodrigues, D; Figueiredo, M; Fabiao, A (Wildfowl, 2001)
Lead pellet ingestion by Mallards of Central Portugal ranged from zero to 100%, 99 being the highest number of lead pellets detected in a single gizzard. On rice fields, lead poisoning risk increased during the shooting season through the accumulation of lead pellets on land surface, since ingested lead pellets were only detected three weeks after the beginning of the season. Livers analyzed showed lead concentrations indicating abnormal and acute exposure to lead contamination which most probably resulted in the indirect and direct cause of death of the birds studied. As this study proved that lead poisoning is a cause of waterfowl mortality also in Portugal, Portuguese authorities should implement, as soon as possible, measures concerning the replacement of lead pellets by alternative non-toxic materials.